Continuous availability of application services via middleware for fog computing environment / Mohd Hariz Naim @ Mohayat - Naim @ Mohayat, Mohd Hariz (2023)
Application services are the processes that run on the operating system background that are required by all types of software applications ranging from desktop applications to web applications and mobile applications. These applications are distributed and scattered around the globe with highly dependent on internet connectivity which is prone to unexpected interruption and downtime. This eventually affects the availability of the application services that need to comply with Service Level Agreement (SLA) as part of the Confidentiality, Integrity and Availability (CIA) security model of a software application. To date, there are available solutions to provide high availability of application services by implementing redundancy model, fault tolerance and overload protection that are focusing on cloud level applications. However, the fault detection and fault tolerance mechanism for fog and edge level with less dependent on internet connectivity are yet to be deeply covered. Before the recovery action take place, the failure detection should be able to detect failure correctly and this can be obtained by monitoring the targeted node through certain methods. Heartbeat detection is one of the detection methods that send periodical message to the monitored node and await for response to indicate node uptime. From the preliminary investigation, it is found that the heartbeat detection when deployed on edge of network produced high false detection and unable to detect software backend service failure. Thus, the overall purpose of this study is to provide mechanism for detecting application service failure and improving high availability to reduce downtime for software applications that are targeting noncloud machine as a platform of deployment.